MoS2 BAND GAP MODIFICATION UPON REPLACEMENT OF SULFUR ATOMS BY TELLURIUM ONES - A. V. Krivosheeva; V. L. Shaposhnikov; V. E. Borisenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The electron energy band gap in one monomolecular layer of molybdenum dichalcogenide MoS2 is reduced upon substitution of S atoms by Te ones from 1,84 to 1,17 eV in the case of MoTe2. Both MoTe2 and MoS2 compounds in a bulk phase are indirect-gap semiconductors while one monomolecular layer of MoS2- x Tex compounds are transforming into direct-gap compounds for x < 0,5 or x > 1,5. The band gap dependence has a linear behavior in the case when the concentration of Te atoms is smaller than the concentration of S atoms.